I, The Dampak Hubungan Kerjasama Tiongkok Dalam Membangun Perekonomian di Pelabuhan Malaka Abad 15 - Indira Rahma Syifa (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2021)
The purpose of this paper is to determine the involvement of the Ming Dynasty in China in taking over the economy at the Port of Malacca, which became the international market trade traffic throughout the XV century. Malacca, as an area around the coast, tries to collaborate with various regions to fulfill their regional missions and needs. The motive also begins with the Ming Dynasty protecting the Kingdom of Malacca from attacks by the Kingdom of Siam and the Majapahit Kingdom which greatly influenced the economy. Cooperation in the economy moves Malacca on a large scale with several regions as well as regions that are also potential competitors in their own trade. . This study uses a historical method to examine its subject matter. Thus the findings of this paper are qualitative in nature with data obtained from various local and international literature.